Critical risk factors influencing the management of disruptions in construction projects: Insights from recent challenges in Sri Lanka - Wasantha Rajapakshe (Social Sciences and Humanities Open, 2025)
The construction industry has a significantly contribute to the economy of Sri Lanka. However, in recent years, its overall share of the national output has declined, primarily due to the impacts of the COVID-19 pandemic, political instability, and ongoing economic challenges. Many construction firms halted projects and laid off employees, highlighting the critical need for effective risk management during crises to predict and mitigate risks. This study explores emerging risk factors in Sri Lanka's construction sector post-crisis. Using a three-phase linear decision-making model, the research combines a literature review, a survey of 290 construction professionals, and structural equation modelling (SEM) to identify major risk factors across four phases of risk management. Key risks out of 23 include general factors like health and safety issues, material costs, regulations, political interference, corruption, and labor shortages, while phase-specific risks involve delays, budget overruns, payment delays, and cancellations. The study revises the risk registers to improve risk management strategies. While the findings are context-specific to Sri Lanka, they may offer indicative insights for other developing countries facing similar crisis-driven disruptions. The practical implications extend to multinational and local companies, supported by data from 22 countries, offering a comprehensive framework for addressing construction industry challenges in volatile environments. The novelty of this study lies in its use of theoretical triangulation to align Classical Risk Management theory with real-world operational risk factors, revealing critical overlaps, behavioral influences, and contextual gaps in traditional frameworks.